Effects of alkaloids on peripheral neuropathic pain: a review - Chunhao Zhu; Ning Liu; Miaomiao Tian; Lin Ma; Jiamei Yang; Xiaobing Lan; Hanxiang Ma; Jianguo Niu; Jianqiang Yu (BMC, 2020)
Abstract Neuropathic pain is a debilitating pathological pain condition with a great therapeutic challenge in clinical practice. Currently used analgesics produce deleterious side effects. Therefore, it is necessary to investigate alternative medicines for neuropathic pain. Chinese herbal medicines have been widely used in treating intractable pain. Compelling evidence revealed that the bioactive alkaloids of Chinese herbal medicines stand out in developing novel drugs for neuropathic pain due to multiple targets and satisfactory efficacy. In this review, we summarize the recent progress in the research of analgesic effects of 20 alkaloids components for peripheral neuropathic pain and highlight the potential underlying molecular mechanisms. We also point out the opportunities and challenges of the current studies and shed light on further in-depth pharmacological and toxicological studies of these bioactive alkaloids. In conclusion, the alkaloids hold broad prospects and have the potentials to be novel drugs for treating neuropathic pain. This review provides a theoretical basis for further applying some alkaloids in clinical trials and developing new drugs of neuropathic pain.